Transgenic Mosquitoes Fight against Malaria: A Review - Shrivastava, Amit Kumar; Shrestha, Laxmi; Prakash, Shraddha; Mehta, Roshan Kumar (Journal of Universal College of Medical Sciences, 2019)
Malaria control with transgenic mosquitoes will be challenging; however, recent advances suggest that it may be a possibility in the foreseeable future. Progress towards discovering refractory genes for rodent malaria and gene drive systems for Drosophila provide hope that similar advances may be made for human malaria in mosquito vector species. That said, the African malaria burden has proved exceptionally difficult to diminish by all means tried thus far; and it is unlikely that transgenic mosquitoes will provide an all-in-one solution. Transgenic mosquitoes should be considered within the context of an integrated vector management strategy which should also include insecticide-treated bed-nets, indoor residual spraying with insecticides and treatment of infected individuals with antimalarial drugs. Integrated strategies will be a necessity for any successful african malaria control program and transgenic mosquitoes should be considered as a potential ingredient in the future goal of continent-wide disease control.